Consumer Socialization: A Comparison Between Indonesian Third Culture Kids (TCKs) and Non-TCKs - Saputri, Dyasanti Vidya; Wandebori, Harimukti (Journal of Business and Management, 2014)
An important determinant of a person’s behavior is influence from others. Consumer socialization is the process by which consumers acquire skills, knowledge and attitudes relevant to their functioning as consumers in the marketplace. These skills, knowledge and attitudes are transmitted from various sources of influence, known as socialization agents—peers, parents, the mass media, and the Internet. Typically, these agents exert two types of influence on the consumer—normative influence and informative influence. An attempt is made in this study to present a comparison between emerging adult Indonesian third culture kids (TCKs) and Non-TCKs in terms of a) their consumer susceptibility to normative and informative influences of the four socialization agents, and b) cross-cultural orientation. The study also explores the correlation between cross-cultural orientation and consumer susceptibility to normative and informative influences. The result of this study indicates that compared to their non-TCK counterparts, Indonesian TCKs receive higher overall informative influence and have higher cross-cultural orientation in terms of both attitude and awareness. On top of that, results show that TCKs also receive higher parents informative and Internet informative influence. Keywords: Consumer Socialization, Socialization Agents, Consumer Susceptibility to Interpersonal Influence, Third Culture Kids